EKOENZIM DAN LILIN AROMATERAPI SEBAGAI PEMANFAATAN LIMBAH RUMAH TANGGA DALAM RANGKA PEMBERDAYAAN MASYARAKAT KAMPUNG INGAS, KARANGTURI, SEMARANG - Anggraini, Baiq Aprilia Noor (PRAXIS: Jurnal Pengabdian kepada Masyarakat, 2024)
Organic waste is one of the most common types of waste produced by households. Statistical data shows that households have been named the main source of the highest waste. Households contribute 39.82% of total waste in Indonesia. Vegetable peels, fruit peels, used cooking oil, etc. are examples of organic waste, but most people don't care about the benefits of this organic waste. Household organic waste can be used to make environmentally friendly enzymes. One of the environmentally friendly enzymes that is useful is ecoenzyme which not only it has many benefits, making ecoenzymes also means taking part in protecting the environment. Ecoenzymes are useful because they are environmentally friendly products that contain anti-fungal, anti-bacterial, insecticidal agents and cleaning agents. Apart from organic waste such as vegetable peels or fruit peels, there is another household organic waste that needs attention, that was used cooking oil. If used cooking oil can be handled properly, it can be used as an ingredient to making a product, one of the product is aromatherapy candles. The partners of this activity are the people of Kampung Ingas, Karangturi, Semarang. The activity method was carried out in three stages: product socialization, ecoenzymes and aromatherapy candles training, and finally product marketing. The output of this activity produces skills to process household waste into simple products that have economic value, which is making ecoenzymes and aromatherapy candles.